СELL CYCLE INDICES OF RATS LUNGS TISSUE CELLS AFTER BURN SKIN LESION - Ocheretnyuk А.О.; Prokopenko, S.V.; Chereshnyuk І.L.; Lysenko D.А. (World of Medicine and Biology, 2014)
The article presents the analysis of the performance of the cell cycle of lungs cells against a background of burning the skin and in the correction of a 0,9 % solution of NaCl, laсtoprotein with sorbitol or HAES-LX 5% at 1, 3 and 7 days after burn skin lesions in rats. It was revealed that the burn damage of the skin accompanied by a significant reduction in DNA synthesis phase indices, normalization which occurs on the 7th day after the defeat. When applied on a background of burn skin lesions lactoprotein with sorbitol in 1 day found a significant increase in proliferation index (PI) and phase G2 + M, and the decline in the G0G1 phase as compared with the group Burn + 0,9% NaCl. On the background of the drug HAES-LX 5% after 3 days after burn skin revealed a strong tendency to decrease proliferation block (p = 0,093) and increased phase G2 + M (p = 0,055) compared with those on day 3 group Burn 0,9% NaCl. Usage of lactoprotein with sorbitol or HAES-LX 5%, 7 days after burn injury of the skin, caused a normalization of cellular cycle of lungs, which was characterized by a decrease of block proliferation index, as well as a positive stimulating effect on DNA synthesis in the application of HAES-LX 5%.